Pemberdayaan Keluarga Melalui Pendidikan Literasi Keuangan dan Pendampingan Belajar Anak di Dusun Bance’e - Mildayanti; Dwiyanti; Alrizqi, Damas Gianlugi; Hidayat, Rahmat; Ridwan, Nurul Haeriyah (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2026)
This Community Service Program aims to empower families in Bance’e Hamlet through financial literacy education and the strengthening of parental involvement in children’s learning. The program was developed in response to the limited financial management skills of families and the low level of parental participation in the learning process at home. The activities were implemented through several stages, including financial literacy workshops, parental training on learning assistance, the establishment of family support groups, field mentoring, and program evaluation. The results indicate an improvement in families’ knowledge and skills in managing household finances. Most participating families began keeping simple financial records, preparing monthly budgets, and allocating funds for their children’s education. Parental involvement in children’s learning also increased, as reflected in the growing frequency and quality of learning interactions at home. In addition, the formation of family support groups helped create a collaborative learning environment within the community. Overall, the program has had a positive impact on strengthening family capacity, both financially and socio-emotionally. The integration of financial literacy education and parental learning assistance has proven to be an effective approach to enhancing the role of families in supporting children’s educational success.